Assimilation Result of Watermarking and Image Compression - Kanniga, E. (International Journal of Psychosocial Rehabilitation, 2019)
In these days’ digital international, trade of statistics is being held electronically. Therefore, there arises the exceptional want for secure transmission of the concerned facts. Various practices like cryptography, watermarking, compression, and so forth. Is it common to see that beyond a few years? All these strategies were proved to be terrific in their respective paintings concerning protection. In this paper, a brand new approach has been provided to provide safety at a stronger stage. Here the two techniques, specifically watermarking and compression, are combined together to decorate the extent of security for statistics transmission motive. Here the watermarking, the usage of the DCT method, is combined with the picture compression technique, the usage of stepped-forward adaptive Huffman encoding. The progressed adaptive Huffman coding approach is based on Huffman’s set of rules. This new compression set of rules no longer most effectively reduces the number of skips required to encode the records, but at the same time reduces the garage area in comparison to adaptive Huffman and static Huffman, respectively. The ultimate result Cozy records transmission